2006
DOI: 10.1093/jn/136.8.2153
|View full text |Cite
|
Sign up to set email alerts
|

Conjugated Linolenic Acid Is Slowly Absorbed in Rat Intestine, but Quickly Converted to Conjugated Linoleic Acid

Abstract: We showed previously that alpha-eleostearic acid (alpha-ESA; 9Z11E13E-18:3) is converted to 9Z11E-conjugated linoleic acid (CLA) in rats through a Delta13-saturation reaction. To investigate this further, we examined the absorption and metabolism of alpha-ESA in rat intestine using a lipid absorption assay in lymph from the thoracic duct. In this study, we used 4 test oils [tung oil, perilla oil, CLA-triacylglycerol (TG), and pomegranate seed oil, containing alpha-ESA, alpha-linolenic acid (LnA; 9Z12Z15Z-18:3)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
88
2
2

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 90 publications
(101 citation statements)
references
References 26 publications
(54 reference statements)
9
88
2
2
Order By: Relevance
“…The data obtained by these authors suggest that punicic acid is slowly absorbed in the rat and mice intestine, but it can be converted into 9c,11t-C18:2n-6 in various tissues, e.g., liver, adipose, kidney and brain. Moreover, punicic acid can be incorporated into plasma and red blood cells, and partially metabolized into CLA in humans (Tsuzuki et al, 2006). These authors found that punicic acid was incorporated into plasma (0.47% total fatty acids (FA)) and red blood cell membranes (RBCM) (0.37% total FA) in humans after supplementation with 3 g punicic acid per day for 28 days.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The data obtained by these authors suggest that punicic acid is slowly absorbed in the rat and mice intestine, but it can be converted into 9c,11t-C18:2n-6 in various tissues, e.g., liver, adipose, kidney and brain. Moreover, punicic acid can be incorporated into plasma and red blood cells, and partially metabolized into CLA in humans (Tsuzuki et al, 2006). These authors found that punicic acid was incorporated into plasma (0.47% total fatty acids (FA)) and red blood cell membranes (RBCM) (0.37% total FA) in humans after supplementation with 3 g punicic acid per day for 28 days.…”
Section: Discussionmentioning
confidence: 99%
“…The in vivo mechanism of punicic acid conversion into CLA is not clear. Some studies suggest that conjugated linolenic acid (CLnA) isomers may be converted into 9c,11t-C18:2n-6 via Δ13-saturation reaction (Tsuzuki et al, 2006;Yuan et al, 2009a). However, the enzyme that catalyses the reaction of Δ13-saturation in animals and humans has not been identified yet.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been shown that PA can be converted into cis 9, trans 11-18:2 in various rat tissues, such as liver, adipose tissue, plasma and brain [14,15] . Also, Yuan et al have shown that PA can be incorporated into plasma and erythrocytes and a part of PA can also be metabolized into cis 9, trans 11-18:2 in humans.…”
Section: Review Articlementioning
confidence: 99%